SELECTIVE RELEASE OF FATTY ACIDS DURING LIPID HYDROLYSIS IN FROZEN-STORED MILK FISH (CHANOS CHANOS) - NAIR, P. G VISWANATHAN; GOPAKUMAR, K (Fishery Technology, 2017)
Lipid hydrolysis and the nature of fatty acids lost as a result of lipid hydrolysis in milk fish ( Chanos chanos) during frozen stroage at-20Â°C is discussed in this paper. There was a preferential loss of saturated acids during the first three weeks of stroage. This was followed by loss of polyunsaturated acids during the next seven weeks. Sharp decrease in the levels of monounsaturated acids was observed from the 10th week of frozen storage. These observations are due to the preferential hydrolysis of phospholipids with relatively high proportion of saturated acids during the first three weeks, followed by the hydrolysis of phospholipids with high proportions of polyunsaturated fatty acids from the 3rd to the 10th week, and :finally, predominant hydrolysis of neutral lipids from the 10th week onwards. Storage of fish in the ice prior to freezing was found to accelerate lipid hydrolysis, especially that of neutral lipids, during frozen storage.